Study of university students' attitudes toward office space at universities - S.M. Eteadifard (Taḥqīqāt-i Farhangī-i Īrān)
Office space is the space where students first experience the university. In this paper, the attitude of students toward office space in the public sphere of university is discussed. This article is the result of the research conducted for the “Institute for Social and Cultural Studies” by the author. The main issues in this paper are: university students' attitudes towards quality office space at the universities and mental basis of common issues among students at the universities. Data were collected through individual and group interviews. More than eighty interviews with activists and students of University of Tehran, Shahid Beheshti University, Allameh Tabataba’i University, Sharif University of Technology and Kharazmi University were done. The main indicators of office space in this study include: students’ satisfaction of office space, students’ welfare affairs and students’ feedback about this space. Problems and obstacles relating to the office space and their solutions were also studied in this paper.